Primary generalised epileptic myoclonus: a frequent manifestation of minipolymyoclonus of central origin. Issue 6 (June 1985) - Wilkins, D E; Hallett, M; Erba, G
Abstract : A group of patients with myoclonus is described whose jerks are preceded by a bilaterally synchronous, frontocentrally predominant, negative cerebral potential in the EEG. This potential may be a slow wave with variable timing in relation to EMG bursts, and in this circumstance the muscle jerks are usually small amplitude and multifocal ("minipolymyoclonus"). The cerebral negativity can also be shorter in duration and time-locked to limb jerks, which are larger in amplitude and more widespread. We propose that the physiology of this distinct form of myoclonus is similar to that of primary generalised epilepsy.